Kajian Teknik Pemberian Hara Terhadap Pertumbuhan dan Perkembangan Nepenthes mirabilis - Mardhiana Mardhiana; Yakup Parto; Renih Hayati; Dwi Putro Priadi (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2015)
The objective of this research was to study the effect of nutrient fertilization on the growth and development of nepenthes (Nepenthes mirabilis). The research was conducted from October 2011 until March 2012 at Sukarami village, Palembang, Indonesia. Factorial randomized block design with two treatment factors was applied. The first factor was NPK fertilizer dosage which consisted of three levels: Po = no fertilizer, P1 = 5 g, P2 = 10 g. The second factor was number of ants: S0 = none, S1 = 20, S2 = 40, S3 = 60. The results indicated that NPK fertilizer application of 5-10 g to the planting media could increase plant growth and development, particularly in plant height, stem girth, and leaf number of N. mirabilis. Giving 60 ants per plants into nepenthes pitcher could yield the largest pitcher number, 3-4 pitcher per plant. Combination of 5 g NPK and 20 ants, similarly, combination of 10 g NPK and 0 ants resulted in the largest leaf increment (10-11 leaves). Combination of 0 NPK and 60 ants resulted in the largest pitcher number (3-4 pitcher per plant).